Awareness and knowledge of academic burnout among student in university malaysia kelantan kampus kota: a qualitative study - Nurfarahim Mohd Zuki; Aiman Insyirah Kharudin; Ain Sabrina Azmi; Malini A/P Baloo (2023)
Academic burnout entails the tiredness and disengagement students endure due to long-term exposure to specified academic expectations. Academic burnout has various negative consequences, including poor academic performance and mental health. The rate of Malaysian students suffering from mental health problems doubled in less than a decade, from 10 percent in 2011 to 20 percent in 2016. This study examined the awareness and knowledge of academic burnout among the University Malaysia Kelantan Kampus Kota students. This study also proposes recommendations and suggestions for preventing student stress and burnout. This study conducted an in-depth interview where print-out questions were given to the respondents. This study used 'purposive sampling' where only Universiti Malaysia Kelantan Kampus Kota students participated. Keywords: Burnout, academic burnout, awareness, knowledge